Isothermal Modelling of the Adsorption of Crystal violet onto Modified Charred Rice Husk (Journal of Environmental Microbiology and Toxicology, 2023)
The rice milling process produces rice husk as a by-product. It is one of the most important agricultural leftovers in terms of volume. The data of the sorption isotherm of crystal violet (CV) sorption onto modified charred rice husk, which was plotted using linearized plots of isothermal models were reanalyzed using twenty isothermal models using nonlinear regression. Nineteen models — Henry, Langmuir, Freundlich, Jovanovic, Redlich-Peterson, Sips, Toth, Hill, Khan, BET, Vieth-Sladek, Radke-Prausnitz, Fritz-Schlunder III, Unilan, Baudu, Marczewski-Jaroniec,  Fritz-Schluender IV, Weber-van Vliet and Fritz-Schluender V – fitted the data best using non-linear regression. Statistical analysis based on error function analyses such as root-mean-square error (RMSE), adjusted coefficient  of determination  (adjR2),  accuracy factor (AF),  bias  factor  (BF), Bayesian Information Criterion (BIC), corrected AICc (Akaike Information Criterion), and Hannan-Quinn Criterion (HQC) showed that Jovanovic model was the best model. The maximal adsorption capacity in the Jovanovic model, expressed in milligrams per gram (mg/g), is denoted by qmJ while Kj is the Jovanovic constant, and the calculated values were 55.979 mg/L (95% confidence interval; 52.556 to 59.403) and 0.010 (95% confidence interval; 0.008 to 0.012), respectively. The nonlinear regression method provides parameter values within the 95% confidence interval, facilitating improved comparability with prior research.
Keywords: Biosorption; Crystal violet; Isotherm; Modified rice husk; Jovanovic isotherm